Non-Gaussian fatigue analysis of packaged fruit under random vibration using an improved CEEMDAN hybrid Gaussian decomposition approach - Song-Ping Yang; Jun-Ye He; He-Mu Yu; Tong Ji; Zhi-Wei Wang (Postharvest Biology and Technology, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Alterations in the ecological amplitude of summer-dormant submerged macrophyte serve as sensitive indicators for the ecological risk of PFAS in water - Zhenhan Li; Hongwei Yu; Diga Gang; Quanlin Lu; He Ji; Jichun Mu; Xiaoyan Zheng; Jing Qi; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2026)

Engineering a 2-methylimidazole framework nanozyme for efficient oxidation of lactose to lactobionic acid under mild conditions - Donghui Xie; Yanna Jiao; Shaoyi Yu; Jia Tu; Yunhui Cheng; Xiaohong He; Daichen Mu; Keyu Xing; Zhou Xu (Journal of Environmental Chemical Engineering, 2026)

Metagenomic insights into the dynamics and persistence of antibiotic resistance genes in wastewater treatment plants - Yinming Mu; Chaoxuan Liao; Yunchuan Long; Yu He; Xiaoxin Cao; Long He; Juan Zhou; Yaqi Chen; Wen Wang; Shaoqi Zhou (Journal of Water Process Engineering, 2026)

Anthropogenic drivers of the composition and distribution of pharmaceuticals and personal care products in landfill leachate in China - Hongxin Mu; Liqun He; Shuai Sun; Shenghu Zhang; Hongqiang Ren; Bing Wu; Houhu Zhang; Yuanqing Bu; Jing Yu (Journal of Environmental Chemical Engineering, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

PCSNet: A lightweight semantic segmentation model for low-altitude remote sensing mixed crop segmentation for rapid acquisition of planting information - Ye Mu; Heyang Wang; Jinghuan Hu; Yu Sun; Caocan Zhu; Hang Zhu; Yunlong Ji; He Gong (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

SikaPointNet++: a method for sika deer point cloud segmentation and body dimensions measurement fusing octree-accelerated sampling and morphological enhancement - Haotian Gong; Yinglun Li; Jinfan Wei; Yu Sun; Tianli Hu; Juanjuan Fan; Zhipeng Li; He Gong; Ye Mu (Computers and Electronics in Agriculture, 2025)

Multi-system toxicity of lead (Pb) in Procambarus clarkii: Integrated analysis of tissue damage, immune dysfunction, oxidative stress, and microbial dysbiosis via multi-omics approaches - Lang Zhang; Ziwei Song; Qiuying Qin; Li He; Juan Tian; Yali Yu; Yingchun Mu; Liqi Zhong; Zongbin Cui; Jinhua Gan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Investigating the variations in microbiome and volatilome characteristics of sauce-flavor Muqu across different grades and production rounds - Yu Mu; Linpei Liu; Junjun He; Hong Zhang; Shirui Yu; Zhiyu Zhu; Ying Huang; Mingyue Mou; Chunlin Zhang (Food Chemistry, 2025)

Comprehensive analysis of greenhouse gases emissions and microbial dynamics in glacier-fed lakes across various ablation stages - Shuang Liu; Fuyuan Mai; Meiqi Huang; Qing Yang; Xiaodong Li; Guangli Mu; Bingya Zhang; Linyuan Lu; Yu Pang; Ding He; Qianggong Zhang; Yiwen Liu; et al. (Water Research, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Hydroquinone Hydroxypropyl-β-cyclodextrin Inclusion Complex Based Topical Cream as an Effective Treatment of Melasma by Releasing Hydroquinone in a Controlled Manner - Yinling Mu; Hongbing Liu; Xianglin Guo; Yiyu Liu; Wanbing Pan; Fan Zhao; Haibing He; Jingxin Gou; Xing Tang; Tian Yin; Yu Zhang (Pharmaceutical Research, 2025)

Comparison of surface energy balance and melt characteristics between debris-covered and debris-free zones on Qingbingtan Glacier No. 72, Mt. Tomor of Tien Shan - Jie He; Puyu Wang; Hongliang Li; Ping Zhou; Jianxin Mu; Fanglong Wang; Puchen Chen; Fengchen Yu; Yuping Dai (Climate Dynamics, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Effects of metal oxides loaded with biochar on adsorption of cationic and anionic metals: A meta-analysis - Yang Yu; Xinwei Chen; Lingxin Zhao; Shufei He; Likui Feng; Weixin Zhao; Huizhi Mu; Qingliang Zhao; Liangliang Wei (Journal of Environmental Management, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

A high-performance flexible coaxial BTO/PAN piezoelectric nanofibers for facial expression analysis - Junfei Lin; Junbin Yu; Fangyuan Chen; Xuying Jia; Jiahe Li; Juanhong Zhao; Jian He; Xiaojuan Hou; Jiliang Mu; Xiujian Chou (Chemical Engineering Journal, 2025)

Dicyclohexyl phthalate derails trophoblast function and lipid metabolism through NDRG1 by targeting PPARα:RXRα - Yu Zhang; Yanqing Geng; Yan Zhang; Yidan Ma; Xin Yin; Zhuxiu Chen; Xinyi Mu; Rufei Gao; Xuemei Chen; Fangfang Li; Junlin He (Toxicology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Association Between Multiple Plasma Toxic Metal and Metalloid Exposures and Hypertension in Elderly Chinese Adults - Yiwen Zhang; Xinyue Mu; Junpu Yu; Aimin Yang; Jingli Yang; Rongjie Wu; Fanhui Luo; Bin Luo; Rentong Chen; Li Ma; Jian He (Biological Trace Element Research, 2025)

Intelligent veins recognition method for slope rock mass geological images in complex background noise - Niu Wen-jing; Chen Yuan-xin; He Ben-guo; Chen Guang-mu; Qiu Zhen-hua; Fan Wen-yu (Computers & Geosciences, 2025)

Scalable, flexible and hierarchically porous Janus membrane inducing Zn-Ion flux redistribution and desolvation for dendrite-free zinc anodes - Jiawei Mu; Miao Yu; Bo Zhao; Yan Dai; Tiantian Li; Xiangcun Li; Xinhong Qi; Xuri Wang; Gaohong He (Chemical Engineering Journal, 2025)

Exposure to environmentally relevant levels of GenX affects placental and offspring development in mice - Yuhan Dai; Junlin He; Fei He; Zhuxiu Chen; Yu Jiang; Yanqing Geng; Jianwei Geng; Yongrui Zhou; Xuemei Chen; Fangfang Li; Yingxiong Wang; Xinyi Mu (Environmental Pollution, 2024)

The effect of circulating cytokines on the risk of systemic lupus erythematosus: Mendelian randomization and observational study - Dan Xue; Yu Qian; Xiao Tu; Mu He; Fengling Xing; Yunqing Ren; Chengda Yuan (Immunogenetics, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A zero-dimensional perovskite with high-efficiency luminescence and transient response for advanced information encryption - Junheng Yuan; Tianchi Wang; Yu Zhang; Shuyi Yao; Lulu Han; Dedan Mu; Hao Song; Jiayi He; Feng Zhang; Xuhui Xu (Chemical Engineering Journal, 2024)

Comprehensive insights into the impact of magnetic biochar on protein hydrolysis in sludge anaerobic digestion: Protein structures, microbial activities and syntrophic metabolisms - Likui Feng; Huizhi Mu; Zhelu Gao; Tianyi Hu; Shufei He; Yu Liu; Shijie You; Qingliang Zhao; Liangliang Wei (Water Research, 2024)

Maternal exposure to ZIF-8 derails placental function by inducing trophoblast pyroptosis through neutrophils activation in mice - Yu Jiang; Yanqing Geng; Rufei Gao; Zhuxiu Chen; Jun Chen; Xinyi Mu; Yan Zhang; Xin Yin; Xuemei Chen; Fangfang Li; Junlin He (Food and Chemical Toxicology, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Nb2CTx MXene coating with inhibition of oxidative stress prepared by Marangoni effect for hemodialysis therapy - Yang He; Hanshu Sun; Yanjie Wang; Ya'nan Yu; Changjun Mu; Li Chen (Chemical Engineering Journal, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Characterizing NOx emissions from diesel trucks with tampered aftertreatment systems and its implications for identifying high emitters - Miao Tian; Liqiang He; Di Peng; Mingliang Fu; Shuai Ma; Jinsong Mu; Quanshun Yu; Jia Wang; Hang Yin; Junfang Wang (Science of The Total Environment, 2024)

Dynamic responses of multi-story structural systems with separated gravity and lateral resisting systems under seismic action considering connection semi-rigidity effects - He Zhao; Xin-Yu Qian; Xiao-Gang Liu; Hong-Bing Chen; Mu-Xuan Tao (Engineering Structures, 2024)

Genome-wide identification of GATA transcription factor family and the effect of different light quality on the accumulation of terpenoid indole alkaloids in Uncaria rhynchophylla - Yingying Shao; Yu Zhou; Li Yang; Detian Mu; Iain W. Wilson; Yao Zhang; Lina Zhu; Xinghui Liu; Ling Luo; Jialong He; Deyou Qiu; Qi Tang (Plant Molecular Biology, 2024)

A biomimetic mineralization nanosystem based on glycolysis-oxidative stress-autophagy regulation for the suppression of malignant tumor and lung metastasis - Ping Guan; Zhaoxu Meng; Xinran Liu; Jiaxiang Mu; Zichun Gao; Xinrong Yu; He Lian (Chemical Engineering Journal, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

Recognizing and managing construction land reduction barriers for sustainable land use in China - Jia-He Zhou; Yu-Ming Zhu; Lei He; Hao-Jing Song; Bing-Xu Mu; Fen Lyu (Environment, Development and Sustainability, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

Experimental study on the suffusion mechanism of gap-graded soils under an exceedance hydraulic gradient - Liang Chen; Yu Wan; Jian-Jian He; Chun-Mu Luo; Shu-Fa Yan; Xian-Feng He (Natural Hazards, 2021)

Correction to: A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

Molecular characterization of a novel fusarivirus infecting the plant-pathogenic fungus Botryosphaeria dothidea - Wenyi Liu; Du Hai; Fan Mu; Xiaojing Yu; Yingtong Zhao; Bangling He; Jiatao Xie; Daohong Jiang; Huixiang Liu (Archives of Virology, 2020)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)